Genetic and immune identification and functional analysis of TRPM8 as a potential biomarker for pancreatic adenocarcinoma proliferation - Sen Qiao; Fengming Wu; Hongmei Wang (Cancer Reports, 2024)
Abstract Background Pancreatic adenocarcinoma (PAAD), a member of highly lethal malignant tumors, has a poor outcome and extremely poor prognosis. The transient receptor potential (TRP) superfamily, a group of nonselective cation channels, is capable of influencing cellular functions by regulating calcium homeostasis. In addition, it has been shown that TRP channels can also affect various cellular phenotypes by regulating gene transcription levels and are involved in the development of a variety of malignant tumors. Aims In order to find new therapeutic targets and biomarkers to improve the clinical prognosis of pancreatic cancer, we performed genetic and immunological characterization of TRP channels in PAAD, as well as related functional and prognostic analyses. Methods and Results We investigated the expression, genetic alterations, methylation levels, and immune infiltration levels of TRP channels in PAAD, and further also analyzed the function of TRP channels in PAAD and their prognostic value for PAAD patients. Our results suggest that TRPM8 may contribute to tumor proliferation by controlling the PI3K‐AKT–mTOR signaling pathway in PAAD. Conclusion After careful evaluation of the accumulated data, we concluded that TRPM8 has potential as a prognostic indicator and prospective therapeutic target in PAAD.